2011
DOI: 10.1111/j.1365-2788.2011.01461.x
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Challenges of residential and community care: ‘the times they are a‐changin’

Abstract: This paper seeks to examine a number of issues which relate to the provision of appropriate and high-quality residential and community care for people with an intellectual disability. A number of key themes emerging from this Special Issue of the Journal of Intellectual Disability Research are identified and explored: (1) normalisation; (2) inclusion; (3) choice; and (4) regulation. It is concluded that the research community has an obligation to assume a higher profile at a time when the quality of life of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In 2010, a similar message was echoed by Lernihan and Sweeney who suggested that, to fully support individuals' needs, the emotional needs of staff should be considered as well. Further, Jackson () called for an exploration of “innovative and practical approaches to enhancing the quality of the services offered” and “strategies that develop essential expressive and relational aspects of care practice” (pp. 941–942).…”
Section: Resultsmentioning
confidence: 99%
“…In 2010, a similar message was echoed by Lernihan and Sweeney who suggested that, to fully support individuals' needs, the emotional needs of staff should be considered as well. Further, Jackson () called for an exploration of “innovative and practical approaches to enhancing the quality of the services offered” and “strategies that develop essential expressive and relational aspects of care practice” (pp. 941–942).…”
Section: Resultsmentioning
confidence: 99%
“…Provider organisations respond by employing many of their staff (particularly those in day‐to‐day contact with their clients) on remuneration close to the minimum wage. This in turn makes it difficult to recruit or retain staff suitable for this type of work (Care Quality Commission, ), but may also generate among staff an alienation characteristic of industrial process work (Jackson, , ).…”
Section: Residential Alternativesmentioning
confidence: 99%
“…Previous studies have revealed that support to staff from their immediate manager may be an important factor for development and improvement of necessary staff skills (Deveau & McGill, ). Studies have also shown that managers’ leadership and way of motivating staff can result in better outcomes for residents in group homes in terms of participation and increased independence (Bigby, Knox, Beadle‐Brown, & Clement, ; Deveau & McGill, ; Jackson, ). Beadle‐Brown et al.…”
Section: Introductionmentioning
confidence: 99%